Tantangan Guru dalam Pembelajaran Sejarah di Era Digital - Irfan Swanto Yusni; M. Rizky Kurniawan; Mukhlisin Nata Hudin; Syarifuddin Syarifuddin; Ferralia Eka Putri (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
The development of digital technology in the Society 5.0 era presents both challenges and opportunities in history teaching, particularly regarding teachers’ ability to integrate technology and adapt to changes in students’ learning styles. This study aims to analyse the challenges faced by teachers and the strategies employed in digital-based history teaching. The method used is a Systematic Literature Review (SLR) employing the PRISMA approach, involving the stages of identification, screening, eligibility assessment, and inclusion of scientific articles published between 2020 and 2025. From the selection process, 25 relevant articles were identified for qualitative descriptive analysis. The findings indicate that teachers’ digital literacy levels remain at a moderate level and are unevenly distributed, thereby affecting the sub-optimal integration of technology into teaching. Furthermore, changes in students’ learning styles which are increasingly technology-oriented require more interactive and contextual pedagogical innovations. On the other hand, the use of digital media has proven capable of enhancing student motivation and learning outcomes, although this is still hindered by limitations in infrastructure and teachers’ technical competencies. The abundance of historical information on the internet also poses challenges regarding the validity of sources, thus necessitating the strengthening of digital literacy and critical thinking. The implications of this research underscore the importance of the ongoing development of teachers’ digital skills, the improvement of educational facilities, and the implementation of innovative teaching models to ensure that history teaching becomes more relevant and effective, and is capable of fostering critical thinking skills in pupils in the digital age.